Physico-chemical and Sensory Characteristics of Jicama and Sweet Orange Velva - Riftyan, Emma; Ayu, Dewi Fortuna; Sitohang, Jeplin (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Velva is a frozen food made from fruit puree, sugar, and stabilizers. Jicama contains a high fiber content, but the flavor is less preferred. Adding Sweet Orange juice can produce Velva high in fiber, vitamins, and flavors liked by the panelist. This study aimed to obtain the best ratio of velva from Jicama puree and Sweet Orange juice. The research used a complete randomized design (CRD) with five treatments and four repetitions to obtain 20 experimental units. The treatment in this study was the ratio of Jicama puree and Sweet Orange juice, namely BJ1 (70:30); BJ2 (60:40); BJ3 (50:50); BJ4 (40:60); and BJ5 (30:70). The data obtained were statistically analyzed using analysis of variance and continue with Duncan's multiple range test at the level of 5%. The results showed that the ratio of Jicama puree and Sweet Orange juice had a significant effect on crude fiber content, total dissolved solids, overrun, melting rate, vitamin C, and descriptive and hedonic sensory assessments such as color, aroma, taste, texture, and overall acceptance. The best ratio of velva was BJ4 with the ratio of Jicama puree and Sweet Orange juice (40:60). BJ4 treatment had crude fiber of 2.39%±0.25; total dissolved solids of 34.26%,±0.98; overrun of 8.88%±0.99; melting rate of 10.01 ml/min±0.60, and vitamin C of 34.32 mg±1.76. The BJ4 treatment had a yellow color, orange aroma, flavor, and soft texture.